A method for fast simulating the liquid seepage-diffusion process coupled with internal flow after leaking from buried pipelines. (10th December 2019) - He, Guoxi; Lyu, Xidi; Liao, Kexi; Li, Yansong; Sun, Liying
Abstract: Once the oil pipeline leakage accident occurs, it is of great significance to predict the leakage volume and the diffusion range of leaked oil accurately and efficiently in order to reduce the contamination degree and formulate the environmental impact assessment and repair scheme. In this paper, a prediction model of leakage intensity of leaked oil and seepage-diffusion range in soil is proposed. Firstly, the entire leakage process inside and outside of buried product oil pipeline is simulated, including the process of pipe flow, orifice outflow, and seepage-diffusion, and thus the model of seepage-diffusion of oil in soil is established. Secondly, the coupling solution of seepage-diffusion in soil both before and after the transient pipe flow being terminated is accomplished via interactively transmitting the key parameters between the pipe flow and the seepage-diffusion process. Thirdly, the comparison of simulated data with experiment results proves that the flow-seepage-diffusion coupled model has better applicability and a higher accuracy in acquiring the severity, quantity, and range of the leakage. Finally, the effects of pressure transmission coefficient, leak orifice's size, leakage flowrate, pipe diameter, leak orifice's position, pipe depth, and diffusion resistance are systematically analyzed. Thus, the characteristics of dynamic seepage-diffusion of leaked oil in porous soil are investigated, which provides an important basis and technical support for pipeline accident treatment. Highlights: A model can predict the seepage-diffusion range of oil pipeline leakage is proposed. Leakage is modeled to three parts: pipe flow, orifice outflow and seepage-diffusion. The model has been verified to have high accuracy by experiments in situ. Seven factors affecting the seepage-diffusion range are analyzed. The subsequent leaking range after the pipe flow being terminated is also available.